Penyesuaian Komunikasi Pegawai Generasi Z dalam Interaksi Lintas Generasi di Institusi Pemerintahan - putra, gema teugoeh; Roem, Elva Ronaning; ., Sarmiati (CV. ITTC INDONESIA, 2025)
Differences in generational characteristics in the workplace, particularly between Generation Z and more senior generations, often lead to communication challenges that affect work effectiveness and employee cohesion. This issue is especially relevant in government institutions, which now comprise various age groups with differing values and communication styles. This study aims to analyze the forms of communication adjustment carried out by Generation Z employees in navigating intergenerational interactions within the bureaucratic environment of government organizations.. The research focuses on the communication strategies used when interacting with colleagues and superiors from older generations. A qualitative approach was employed using a transcendental phenomenological method, grounded in the Communication Accommodation Theory (CAT). Data were collected through in-depth interviews with key informants from Generation Z employees. The data analysis followed the stages of transcendental phenomenology using a modified Stevick–Colaizzi–Keen method as proposed by Moustakas. The findings indicate that communication adjustments are made through strategies of convergence, divergence, and maintenance. Convergence is used to build harmonious relationships and show respect toward senior colleagues. Divergence is employed as a form of identity expression and as a response to value differences. Meanwhile, maintenance is applied as a strategy to preserve comfort in communication. These findings reveal that the dynamics of intergenerational communication are influenced by social needs, identity formation, and the demands of professionalism in multigenerational government organizations.